Poverty incidence and sectoral growth: Evidence from Southeast Asia - Peter G. Warr (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In recent decades, absolute poverty incidence declined in most countries of Southeast Asia, even though in some of these countries inequality increased at the same time. This paper examines the relationship between these outcomes and the rate of economic growth in the agricultural, industrial and services sectors. It develops a time series of available data on the headcount measure of poverty incidence for Thailand, Indonesia, Malaysia and the Philippines over the period from the 1960s to 1999, in aggregate and in both rural and urban areas. It then uses this pooled data set to analyze the economic determinants of changes in poverty incidence.
Keywords: O15; D31; 330; poverty incidence; economic growth; rural poverty; urban poverty; Städtische Armut; Ländliche Armut; Wirtschaftswachstum; Branche; Südostasien